Determinants of Urban Governance in a Sociological Perspective - Karwińska, Anna (Journal of Public Governance, 2009)
The paper focuses on problems of governance in contemporary cities. Both concepts: ‘governance’ and ‘city’,refer to a socio-spatial entity and are complex and require a broader discussion and analysis. Therefore, it was neccessary to choose some aspects for the present consideraton. In the first part of the paper the concept of governance has been discussed from a sociological point of view. Then, in the second part, we discussed and reviewed some possible applications of the principles and main rules of governance to in various spheres of urban life. Finally, some factors influencing the development of urban governance practices were presented and barriers typical for postsocialist cities were identified.